SURVEY AND SUMMARY: Recent advances in the elucidation of the mechanisms of action of ribozymes - Takagi, Yasuomi (Oxford University Press, 2001)
The cleavage of RNA can be accelerated by a number of factors. These factors include an acidic group (Lewis acid) or a basic group that aids in the deprotonation of the attacking nucleophile, in effect enhancing the nucleophilicity of the nucleophile; an acidic group that can neutralize and stabilize the leaving group; and any environment that can stabilize the pentavalent species that is either a transition state or a short-lived intermediate. The catalytic properties of ribozymes are due to factors that are derived from the complicated and specific structure of the ribozyme–substrate complex. It was postulated initially that nature had adopted a rather narrowly defined mechanism for the cleavage of RNA. However, recent findings have clearly demonstrated the diversity of the mechanisms of ribozyme-catalyzed reactions. Such mechanisms include the metal-independent cleavage that occurs in reactions catalyzed by hairpin ribozymes and the general double-metal-ion mechanism of catalysis in reactions catalyzed by the Tetrahymena group I ribozyme. Furthermore, the architecture of the complex between the substrate and the hepatitis delta virus ribozyme allows perturbation of the pK(a) of ring nitrogens of cytosine and adenine. The resultant perturbed ring nitrogens appear to be directly involved in acid/base catalysis. Moreover, while high concentrations of monovalent metal ions or polyamines can facilitate cleavage by hammerhead ribozymes, divalent metal ions are the most effective acid/base catalysts under physiological conditions.